Pulmonary thromboembolism in a dog with inflammatory bowel disease - Sainz, A.; García-sancho , M.; Rodríguez-bertos , A.; Rodríguez-Franco , A.; Villaescusa, A. (Revista Complutense de Ciencias Veterinarias, 2010)
A 4-year-old 4-kg male Yorkshire Terrier was brought for a re-evaluation of inflammatory bowel disease (IBD) diagnosed two years before. The dog presented with a fourweek history of diarrhoea, biliary vomiting, weight loss and ascites. Laboratory analysis revealed hypoproteinemia and a neutrophilic leucocytosis. An upper gastrointestinal endoscopic examination was performed. During the endoscopic procedure, the animal died due to a cardiopulmonary arrest. The necropsy confirmed the presence of a pulmonary thromboembolism. Extraintestinal manifestations of IBD are well reported in humans, but rarely appear in dogs. In Human Medicine, a very common extraintestinal manifestation of IBD is the presence of thromboembolisms. Further studies are needed to evaluate the tromboembolism risk in dogs with IBD.